2006
DOI: 10.1038/ncb1441
|View full text |Cite
|
Sign up to set email alerts
|

A regulated interaction with the UIM protein Eps15 implicates parkin in EGF receptor trafficking and PI(3)K–Akt signalling

Abstract: Mutations in the parkin gene are responsible for a common familial form of Parkinson's disease. As parkin encodes an E3 ubiquitin ligase, defects in proteasome-mediated protein degradation are believed to have a central role in the pathogenesis of Parkinson's disease. Here, we report a novel role for parkin in a proteasome-independent ubiquitination pathway. We have identified a regulated interaction between parkin and Eps15, an adaptor protein that is involved in epidermal growth factor (EGF) receptor (EGFR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
287
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(305 citation statements)
references
References 35 publications
15
287
2
1
Order By: Relevance
“…EPS15 also associates with the clathrin adaptor protein AP-2 on receptor activation and may bind ubiquitinated EGFR through ubiquitin-interacting motifs (UIMs) to promote receptor endocytosis [90]. Parkin, an E3 ubiquitin ligase, promotes signaling through the PI(3)K/Akt pathway by activated EGFR by binding the UIM of EPS15 and limiting receptor endocytosis [91]. Surprisingly, endocytosis does not require activation of the EGFR tyrosine kinase domain, and rather appears dependent on receptor dimerization [84,85].…”
Section: Signal Attenuationmentioning
confidence: 99%
“…EPS15 also associates with the clathrin adaptor protein AP-2 on receptor activation and may bind ubiquitinated EGFR through ubiquitin-interacting motifs (UIMs) to promote receptor endocytosis [90]. Parkin, an E3 ubiquitin ligase, promotes signaling through the PI(3)K/Akt pathway by activated EGFR by binding the UIM of EPS15 and limiting receptor endocytosis [91]. Surprisingly, endocytosis does not require activation of the EGFR tyrosine kinase domain, and rather appears dependent on receptor dimerization [84,85].…”
Section: Signal Attenuationmentioning
confidence: 99%
“…As illustrated below, nitrosative/oxidative stress, commonly found during normal aging, can mimic rare genetic causes of disorders, such as PD, by promoting protein misfolding in the absence of a genetic mutation. 17,18,20 Recently, Fallon et al 67 reported that the protein parkin can mediate neuronal survival via a proteasome-independent pathway. In this model, parkin monoubiquitinates the epidermal growth factor receptor (EGFR)-associated protein, Eps15, leading to inhibition of EGFR endocytosis.…”
Section: S-nitrosylation As a Potential Positive Regulator Of Excitotmentioning
confidence: 99%
“…Downregulation of parkin may also result in a decrease in the neuroprotective activity of Akt because of enhanced EGFR internalization and thus less Akt signaling. 67 DA quinone can also modify the cysteine thiols of parkin and reduce its activity. 72 Ub: ubiquitin this reaction inhibits both its isomerase and chaperone activities.…”
Section: S-nitrosylation As a Potential Positive Regulator Of Excitotmentioning
confidence: 99%
“…Two E3 ligases, NEDD4 and Parkin, have been implicated in the monoubiquitylation of EPS15 (Fallon et al . 2006; Woelk et al . 2006).…”
Section: Regulation Of Membrane‐associated Processes By Monoubiquitylmentioning
confidence: 99%
“…Another mechanism by which Parkin inhibits apoptosis was shown by the finding that Parkin monoubiquitylates and thereby inactivates the endocytic adaptor protein EPS15 (Fallon et al . 2006). EPS15 is an important regulator of growth factor receptor internalization, as described above, and its inactivation by Parkin therefore enhances survival signaling emanating from cell surface receptors—enhancement that is compromised by Parkin mutations.…”
Section: Regulation Of Neuronal Proteins By Monoubiquitylationmentioning
confidence: 99%